Perception of the Use of Artificial Intelligence for Improving English Academic Writing Skills: Persepsi Penggunaan Kecerdasan Buatan untuk Meningkatkan Keterampilan Menulis Akademik Bahasa Inggris - Muhammad Fatikh Anwari; Woro Retnaningsih (Language Development Center, 2025)
Background: The rapid development of artificial intelligence (AI) has significantly influenced various aspects of education, particularly in academic writing. English language education students are increasingly utilizing AI-based tools to support their writing activities. Purpose: This research aims to explore the perceptions of fourth-semester English Language Education students at UIN Raden Mas Said Surakarta regarding the use of AI in improving their academic writing skills. Method: This study employs a descriptive qualitative method using in-depth analysis based on the Technology Acceptance Model (TAM). Data were collected through interviews with ten English students who actively use AI tools in their academic writing. Results and Discussion: The findings show that students use a variety of AI applications such as ChatGPT, Grammarly, Zotero, and others to assist in idea generation, language accuracy, paraphrasing, and reference management. Students acknowledged the benefits of AI in terms of increased productivity, enhanced writing quality, and overcoming writing challenges. However, several concerns were also raised, including overdependence on AI, reduced critical thinking, ethical issues regarding originality, and limited access to premium AI tools. Conclusions and Implications: The study concludes that while AI holds great potential in supporting students' academic writing, it must be balanced with ethical awareness to preserve originality and independent thinking. These findings suggest the need for proactive roles from governments and educational institutions in formulating guidelines for the responsible use of AI in academic settings Keyword : Artificial Intelligence, Student Perception, Academic Writing